2008
DOI: 10.2478/s11756-008-0164-2
|View full text |Cite
|
Sign up to set email alerts
|

An enzyme family reunion — similarities, differences and eccentricities in actions on α-glucans

Abstract: α-Glucans in general, including starch, glycogen and their derived oligosaccharides are processed by a host of more or less closely related enzymes that represent wide diversity in structure, mechanism, specificity and biological role. Sophisticated three-dimensional structures continue to emerge hand-in-hand with the gaining of novel insight in modes of action. We are witnessing the "test of time" blending with remaining questions and new relationships for these enzymes. Information from both within and outsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 77 publications
1
3
0
Order By: Relevance
“…Moreover, another preliminary work indicated that the starch binding to SBS2 in AMY2 is weaker than in AMY1. This finding was also confirmed by its crystal structure [ 32 ].…”
Section: Surface-binding Site In α -Amylasesupporting
confidence: 65%
“…Moreover, another preliminary work indicated that the starch binding to SBS2 in AMY2 is weaker than in AMY1. This finding was also confirmed by its crystal structure [ 32 ].…”
Section: Surface-binding Site In α -Amylasesupporting
confidence: 65%
“…Despite an extremely large number of available sequences (more than 4,500 CAZy entries) and almost 30 different enzyme specificities, the α-amylase family members possess several typical common features. These are (Svensson 1994;Kuriki & Imanaka 1999;MacGregor et al 2001;Janecek 1997Janecek , 2002avan der Maarel et al 2002;MacGregor 2005;Kuriki et al 2006;Seo et al 2008): (i) acting on α-glucosidic linkages, i.e. their hydrolysis or formation by transglycosylation; (ii) possessing from 4 up to 7 conserved sequence regions; (iii) adopting the parallel (β/α) 8 -barrel domain (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Within GHs, the most abundant family across all nine microbiomes were GH13 (517 ORFs), of which 171 and 125 ORFs were found in T 9 -37 (in red) and T 9 -50 (in green), respectively (Figure 10 and Table 4). This family, together with GH4, GH31, GH57, GH63, GH97, and GH126, can be linked to starch degradation by encompassing starch-and pullulanmodifying enzymes, including α-amylases, pullulanases, α-1,6-glucosidases, neopullulanases, and cyclodextrinases [38]. From a biotechnological point of view, amylases are among the most important enzymes for the food industry and recently have found applications also in biofilm inhibition [39].…”
Section: Meta-functional Analysis Of Cazymesmentioning
confidence: 99%